Examining differences between pre- and in-service teachers' cognition when lesson planning. (July 2020) - Contreras, Karen; Arredondo, Claudia; Díaz, Claudio; Inostroza, María Jesús; Strickland, Brandee
Abstract: Lesson planning is an essential part of education and indicates the path teachers will follow throughout a lesson. Due to the time and dedication of planning a lesson and its importance in the teaching and learning process, understanding and acknowledging teachers' cognition while planning at different stages of their careers is needed. The objective of this study was to examine in-service and pre-service teachers' cognitive processes while lesson planning with the use of the think-aloud protocol. Frequency and content analysis were used as data analysis techniques. A total of 28 English teachers and 86 student teachers had to plan a lesson verbalizing their thoughts while being recorded. After this task was fulfilled, the recordings were transcribed and the transcripts analyzed and coded. This data was later organized into categories and subcategories, and counted to analyze how often various cognitive processes appeared. The findings show that while both groups of participants (in-service and pre-service teachers) displayed a wide range of cognitive processes while planning, pre-service teachers were more likely to plan every aspect of the class in detail. However, in-service teachers were more concise at the moment of planning.